2005
DOI: 10.1097/01.aog.0000173799.82687.dc
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Misoprostol Compared With Manual Vacuum Aspiration for Incomplete Abortion

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
101
1
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(127 citation statements)
references
References 7 publications
12
101
1
13
Order By: Relevance
“…This dose has successfully evacuated the uterus in over 1000 women in over a half a dozen trials worldwide. 9,10,19,20,11 Recently completed trials testing 400 mcg sublingual misoprostol compared to 600 mcg oral misoprostol found that that the 400 micrograms sublingual dose is as effective as 600 micrograms oral misoprostol when used for treatment of incomplete abortion. 22 Although the data in support of the 400 microgram sublingual misoprostol dose are less extensive, it may be shown in the future to be the optimal dose and route of administration for this indication.…”
Section: Dosage Regimen 11 17 18mentioning
confidence: 99%
See 3 more Smart Citations
“…This dose has successfully evacuated the uterus in over 1000 women in over a half a dozen trials worldwide. 9,10,19,20,11 Recently completed trials testing 400 mcg sublingual misoprostol compared to 600 mcg oral misoprostol found that that the 400 micrograms sublingual dose is as effective as 600 micrograms oral misoprostol when used for treatment of incomplete abortion. 22 Although the data in support of the 400 microgram sublingual misoprostol dose are less extensive, it may be shown in the future to be the optimal dose and route of administration for this indication.…”
Section: Dosage Regimen 11 17 18mentioning
confidence: 99%
“…5,9,10,12,14,19,20,[25][26][27][28][29][30][31][32][33][34][35][36][37][38]41 (Table 1) The success rate reported in trials is closely related to the length of time after treatment at which the uterus is reassessed by ultrasound exam. 16 Early studies on the use misoprostol for incomplete abortion tested a range of doses (400 mcg to 1200 mcg) and routes (oral, vaginal, intrauterine, etc.…”
Section: 2b Reports Of Efficacy From Studies Comparing Misoprostolmentioning
confidence: 99%
See 2 more Smart Citations
“…The advent of vacuum aspiration in the 1960s revolutionised the The vacuum aspiration method is also a safe, effective, and acceptable treatment for the treatment of first-trimester uncomplicated incomplete abortion, as is 600 µg oral misoprostol. [22][23][24] MVA is faster, safer, more comfortable, and associated with shorter hospital stay for induced abortion than sharp curettage. 25,26 Additional advantages compared with sharp curettage are its ease of use as an outpatient procedure, the need for less analgesia and anaesthesia, 27 and its lower cost per procedure, especially if done on an outpatient basis.…”
Section: Scope Of Induced Abortionsmentioning
confidence: 96%